The Effectiveness of Applying Handball Shooting Skills Training Model to Improve Beginner Athlete Shooting Skills - Lanos, Muhsana El Cintami; Oktariyana, Oktariyana; Lestari, Hikmah (Universitas Negeri Semarang, 2021)
This research uses quantitative methods. This study aims to determine the effectiveness of the application of the handball shooting skills training model to improve the shooting skills of novice athletes. The research design in this study was the one group control pretest-posttest. The research has been carried out in several handball sports clubs in Palembang, South Sumatera. Based on the results of the test of the effectiveness of the application of the handball shooting skills training model that has been carried out, the N-Gain Score test results obtained on the results of the shooting skills obtained by an average N-Gain Score for the experimental class of 86.88% with the